Pengelolaan Hama dan Penyakit Tanaman dalam Menunjang Pengembangan Pertanian Organik Berkelanjutan Berdasarkan Analisis Penguatan Kelembagaan Petani di Kabupaten Konawe Selatan - La Ode Santiaji Bande; La Ode Alwi; Hartina Batoa (AGRIMOR, 2020)
Management of plant pests and diseases is very important role in efforts to maintain agricultural production. Consumers want a chemical-free agricultural production that can generally be obtained from sustainable organic farming. Institutional strengthening through the practice of organic and sustainable agriculture includes increasing the role and rules of the game as well as re-functioning the roles of the community in the development and utilization of vegetable pesticides that support organic agriculture. The purpose of this study is to analyze the institutional index actual and analyze institutional strengthening in the management of plant pests and diseases in supporting the development of sustainable organic agriculture. This research uses primary data and secondary data. Primary data collection methods are interviews with farmers and through Focus Group Discussion (FGD). Primary data consist of, general condition of research location, area of organic agricultural land and organic agricultural production. Data analysis methods used a weighted approach while strengthening institutional control of pests and plant diseases in support of sustainable organic agriculture were analyzed through the Interpretative Structure Modeling (ISM) reliability matrix approach. The results showed that in the reserach location an institution had been formed even though the index category was not good, namely the farmer group, organic farming union and agricultural village with values of 26.25%, 28.32%, and 32.83% respectively index while institutional improvement in motivation has 44.64% which shows a reasonably good performance. In order to strengthenthe management of plant pests and diseases institutions in supporting the implementation of organic agriculture, key indicators that must be carried out consecutively are: availability of regional regulations on pest control and plant diseases, Role of Village Milim Business Entity in plant pestsand diseases management, assistance, plant pests and diseasesmanagement planning, availability of organic farming markets, certainty of organic production prices, organic farming organizations and increasing community participation in plant pests and diseases management.